Whole genome sequencing analysis of salmonella enterica serovar typhi: history and current approaches - Wan Makhtar, Wan Ratmaazila; Bharudin, Izwan; Samsulrizal, Nurul Hidayah; Yusof, Nik Yusnoraini (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
In recent years, the advance in whole-genome sequencing technology has changed the study of infectious diseases. The emergence of genome sequencing has improved the understanding of infectious diseases, which has revamped many fields, such as molecular microbiology, epidemiology, infection control, and vaccine production. In this review we discuss the findings of Salmonella enterica serovar Typhi genomes, publicly accessible from the initial complete genome to the recent update of Salmonella enterica serovar Typhi genomes, which has greatly improved Salmonella enterica serovar Typhi and other pathogen genomic research. Significant information on genetic changes, evolution, antimicrobial resistance, virulence, pathogenesis, and investigation from the genome sequencing of S. Typhi is also addressed. This review will gather information on the variation of the Salmonella enterica serovar Typhi genomes and hopefully facilitate our understanding of their genome evolution, dynamics of adaptation, and pathogenesis for the development of the typhoid point-of-care diagnostics, medications, and vaccines.